Deletion of inducible nitric-oxide synthase in leptin-deficient mice improves brown adipose tissue function. - Sara Becerril; Amaia Rodríguez; Victoria Catalán; Neira Sáinz; Beatriz Ramírez; María Collantes; Iván Peñuelas; Javier Gómez-Ambrosi; Gema Frühbeck (PLoS ONE, 2010)
Background Leptin and nitric oxide (NO) on their own participate in the control of non-shivering thermogenesis. However, the functional interplay between both factors in this process has not been explored so far. Therefore, the aim of the present study was to analyze the impact of the absence of the inducible NO synthase (iNOS) gene in the regulation of energy balance in ob/ob mice. Methods and findings Double knockout (DBKO) mice simultaneously lacking the ob and iNOS genes were generated, and the expression of molecules involved in the control of brown fat cell function was analyzed by real-time PCR, western-blot and immunohistochemistry. Twelve week-old DBKO mice exhibited reduced body weight (p<0.05), decreased amounts of total fat pads (p<0.05), lower food efficiency rates (p<0.05) and higher rectal temperature (p<0.05) than ob/ob mice. Ablation of iNOS also improved the carbohydrate and lipid metabolism of ob/ob mice. DBKO showed a marked reduction in the size of brown adipocytes compared to ob/ob mutants. In this sense, in comparison to ob/ob mice, DBKO rodents showed an increase in the expression of PR domain containing 16 (Prdm16), a transcriptional regulator of brown adipogenesis. Moreover, iNOS deletion enhanced the expression of mitochondria-related proteins, such as peroxisome proliferator-activated receptor gamma coactivator-1 alpha (Pgc-1alpha), sirtuin-1 (Sirt-1) and sirtuin-3 (Sirt-3). Accordingly, mitochondrial uncoupling proteins 1 and 3 (Ucp-1 and Ucp-3) were upregulated in brown adipose tissue (BAT) of DBKO mice as compared to ob/ob rodents. Conclusion Ablation of iNOS improved the energy balance of ob/ob mice by decreasing food efficiency through an increase in thermogenesis. These effects may be mediated, in part, through the recovery of the BAT phenotype and brown fat cell function improvement.